(untitled) (Conferencea, 2023)
Tourism is an integral part of modern civilization. It is important because of the global scale it acquired in the 20th century. Tourism is a leading sector of the economy, both in the world and in Georgia. It develops and improves. Tourism is closely related to the economic and political stability of countries, the level of culture and education of the population. It is a stable sector of the world economy.